Geochemistry of lunar meteorite Yamato-791197: Comparison with ALHA81005 and other lunar samples - Warren,Paul H.; Kallnmeyn,Gregory W. (1986)
P(論文) Yamato-791197 is a regolith breccia from the Earth's Moon. Because lunar exploration has been of limited scope, lunar meteorites are extremely valuable sources of information about lateral variations in composition and petrology of the Moon's crust. We used INAA to analyze a 197mg bulk-rock sample, and two 7mg clasts, from Y-791197. The clasts are both anorthositic impact melt breccias. One of them contains feldspars of unusual "ternary" composition, probably derived from rare lunar granites. It is unclear whether Y-791197 is from the same lunar impact as the first meteorite discovered from the Moon, ALHA81005. In most respects the compositions of these two meteorites are remarkably similar. The source crater (s) must be far from the K, Th, and U-rich region, near the center of the nearside, that supplied the Apollo samples. Volatile element contents are higher in Y-791197 than in ALHA81005,and Y-791197 has a much lower mg ratio (0.64) than ALHA81005 (0.73). The mg disparity suggests that these two "fossil" soils formed many hundreds of meters apart (for comparison, Apollo 16 traverses spanned points up to 8km apart, yet the total range in mg among 20 analyzed regolith breccias from Apollo 16 is 0.65-0.72), or else the impact responsible for propelling them Earthward happened to occur close to a boundary between compositionally dissimilar terrains (e. g., a mare-highlands boundary). The high aluminum (plagioclase) content of Y-791197 tends to confirm the magmasphere model of earliest lunar evolution. departmental bulletin paper